Sphingosine Kinases: Emerging Structure–Function Insights. Issue 5 (May 2016) - Adams, David R.; Pyne, Susan; Pyne, Nigel J.
Abstract : Sphingosine kinases (SK1 and SK2) catalyse the conversion of sphingosine into sphingosine 1-phosphate and control fundamental cellular processes, including cell survival, proliferation, differentiation, migration, and immune function. In this review, we highlight recent breakthroughs in the structural and functional characterisation of SK1 and these are contextualised by analysis of crystal structures for closely related prokaryotic lipid kinases. We identify a putative dimerisation interface and propose novel regulatory mechanisms governing structural plasticity induced by phosphorylation and interaction with phospholipids and proteins. Our analysis suggests that the catalytic function and regulation of the enzymes might be dependent on conformational mobility and it provides a roadmap for future interrogation of SK1 function and its role in physiology and disease. Trends: Sphingosine kinase 1 (SK1) is closely related in tertiary structure to prokaryotic members of the DAGK_cat enzyme family. A dimeric quaternary structure, similar to that of prokaryotic DAGK_cat proteins, may play a role in curvature-dependent targeting of SK1 to the plasma membrane. Access to the Sph binding site likely involves a gating mechanism through opening and closure of a key lipid binding loop sequence (LBL-1). Plasticity in the kinase T-loop may be important to catalytic operation and modulated by a helix-capping mechanism involving the regulatory C-terminal protein-binding sequence. Structural transition elicited by phosphorylation of Ser225 and protein binding to the C-terminal sequence may potentially both unmask membrane association determinants in SK1.